Physical quality of eggs of four strains of poultry - Guilherme Resende de Almeida; Michele de Oliveira Mendonça; Lidianne Carolina de Castro Weitzel; Tatiana Marques Bittencourt; Anderson Soares de Matos; Jean kaique Valentim; Michelle Lopes de Araújo; Adna Quesia Costa de Oliveira (Acta Scientiarum. Animal Sciences, 2021)
The layer poultry is an important activity for food production with high biological value. Measuring egg quality has great relevance to ensure safety and quality products for consumers. Thus, the objective was to evaluate the egg physical quality of four laying hen’s strains. Were used 864 eggs from four laying hens’ lines (Hisex Brown®, Hy-Line Brown®, Isa Label®, and Lohmann Brown®). The experimental design was completely randomized composed of four treatments (strains) with nine replications with four eggs each. Egg weight, egg diameter, egg length, specific gravity, yolk, albumen and shell weight and percentage, Haugh units, and shell thickness were evaluated. There was a significant difference for all parameters evaluated. The Hisex Brown® strain showed the best results for egg diameter, egg length, specific weight, albumen height, Haugh units, yolk weight, albumen%, shell weight, shell%, and shell thickness, while the Hy-Line Brown® produced bigger and heavier eggs, and Isa Label® presented the highest yolk%. The Hisex Brown® strain showed the better physical quality of eggs when compared to the other studied lines, the strain being indicated when the objective is to produce eggs with better internal and external quality.